Major insects pests of maize in Africa: biology and control - Bosque Pérez, N.A. (1995)
Insect pests severely limit the production of maize, one of the most important cereal crops world-wide. Losses reach millions of dollars annually. Control includes cultural, chemical, and biological methods in addition to plant resistance. Integrated pest management combines control methods in an environ-mentally sound manner. Effective control requires knowledge on damage, biology, distribution, and life cycles of insects.